2015
DOI: 10.1073/pnas.1507726112
|View full text |Cite
|
Sign up to set email alerts
|

Balancing between affinity and speed in target DNA search by zinc-finger proteins via modulation of dynamic conformational ensemble

Abstract: Although engineering of transcription factors and DNA-modifying enzymes has drawn substantial attention for artificial gene regulation and genome editing, most efforts focus on affinity and specificity of the DNA-binding proteins, typically overlooking the kinetic properties of these proteins. However, a simplistic pursuit of high affinity can lead to kinetically deficient proteins that spend too much time at nonspecific sites before reaching their targets on DNA. We demonstrate that structural dynamic knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(160 citation statements)
references
References 66 publications
(137 reference statements)
9
145
0
Order By: Relevance
“…This estimate is consistent with typical D 1 values determined by fluorescence methods for other relatively small proteins. 9,20,33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This estimate is consistent with typical D 1 values determined by fluorescence methods for other relatively small proteins. 9,20,33 …”
Section: Resultsmentioning
confidence: 99%
“…Previous biophysical or biochemical studies showed that D 1 is typically on the order of 10 4 –10 6 bp 2 s −1 (e.g., see Refs. 9,20,2629 ).…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…8B, the Miz1-4 construct binds to all of the sequences tested, including two unrelated and nonspecific sequences, with a similar low apparent affinity in the micromolar range. Reported affinities for series of three ZFs to nonspecific DNA sequences normally lie in the low micromolar range, whereas their specific binding rather lies in the nanomolar to picomolar range (17,(32)(33)(34). Hence, our data clearly demonstrate that Miz-1 ZFs 1-4 bind DNA with an affinity and a specificity that are not sufficient to promote specific molecular recognition of the consensus DNA or the p15 core promoter regions by this transcription factor.…”
Section: Miz-1 Zf 1 Undergoes Microsecond To Millisecondmentioning
confidence: 74%
“…However, because those recognition modes involve ZFs 1-6 and the matches do not correlate well with the conserved regions, we believe that these binding modes, although less stable, could serve in the DNA scanning. In this regard, Zandarashvili et al (34,36) recently published studies demonstrating the importance of the presence of a lower affinity DNA binding ZF for optimal target search efficiency by a protein containing three ZFs. Analogously, we propose that ZFs 1-6 serve a similar purpose for the efficient recognition of the consensus by subsets of ZFs 7-12.…”
Section: Miz1-4 Does Not Interact Directly With the Mh1 Of Smad 3-basmentioning
confidence: 99%
“…Experiments also indicate that the nonspecifically bound proteins are involved in conformational transitions between searching conformations with weak protein–DNA interactions, when the proteins slide quite fast along DNA, and stronger interacting recognition conformations, when the proteins move much slower. 17,20,21,23,31 The protein molecule can identify the specific target site only in the recognition mode. However, it seems that these conformational fluctuations should make the search less efficient.…”
mentioning
confidence: 99%